The effects of bicycle crank arm length on oxygen consumption - Morris, D. M.; Londeree, B. R. (Canadian Journal of Applied Physiology, 1997)
The purpose of this investigation was to determine the effects of various crank arm lengths on oxygen consumption for trained cyclists. Secondary purposes were, if optimal crank arm lengths existed, to determine if these lengths could be predicted based on an individual's leg length. Six trained cyclists completed four experimental protocols riding at a workload of approximately 68% of VO2 max using crank arm lengths of 165, 170, and 175 mm. During each protocol, the cadence, oxygen consumption, and distance traveled were determined, and values were combined to give a VO2.m-1.min-1 value. The values then were placed in either a high, medium, or low efficiency category. Significant differences were found among the three protocols. No significant correlations were found between each subject's most efficient crank arm length and leg length. The results of the study suggest that each subject has a most efficient crank arm length, but it does not appear that optimal crank arm length can be predicted by leg length.